Antimony and arsenic particle size distribution in a mining contaminated freshwater river: Implications for sediment quality assessment and quantifying dispersion. (15th July 2022) - Doherty, Steven; Rueegsegger, Isabelle; Tighe, Matthew K.; Milan, Luke A.; Wilson, Susan C.
Abstract: Assessments of antimony (Sb) and arsenic (As) contamination in sediments are reported on a wide range of different particle size fractions, including <63 μm, < 180 μm and <2 mm. Guidelines vary between jurisdictions which limits comparative assessment between contamination events and complicates ecotoxicity assessment, and almost no information exists on Sb size distribution in contaminated sediments. This study quantified and compared the size distribution of Sb and As in 11 sediments (and 2 floodplain soils) collected along 320 km of waterway contaminated by historic mining activity. Sediment particle size distribution was the primary determinant of total metalloid load in size fractions across the varying substrates of the waterway. Minerals and sorption complexes influenced metalloid particle distribution but relative importance depended on location. Arsenic concentrations were greatest in the fine <63 μm fraction across all the different river environments (7.3–189 mg kg −1, or 1–26% of total sample As), attributed to fine-grained primary arsenopyrite and/or sorption of As(V) to fine solid-phases. The Sb particle size concentrations were greatest in mid-size fractions (205–903 mg kg −1 ) in the upper catchment and up to 100 km downstream to the mid-catchment as a result of remnant Sb minerals. Antimony concentrations in the lower catchment were greatest in the <63 μm fraction (8.8–12.1 mg kg −1 ), reflecting the increasing importance of sorption for Sb particle associations. This work demonstrates the importance of particle size analysed for assessment of sediment quality, and provides support for analysis of at least the <250 μm fraction for Sb and As when comparing pollutant distribution in events impacted by primary contamination. Analysis of the <63 μm fraction, however, provides good representation in well-dispersed contaminated sediments. Graphical abstract: Image 1 Highlights: Sb and As show dissimilar particle size distribution in mining-impacted sediments. As concentrations were greatest in the <63 μm fraction throughout the catchment. Sb distribution varied depending on distance from primary contamination zone. Balance between mineralised and sorbed species influenced metalloid distribution. Metalloid mineralisation and source proximity impact sediment quality assessment.